Kelloway, Arthur. Interview about growing up in Salmon Cove - Harvey, Katherine A. (1992-) (2017)
Interview with Arthur Kelloway conducted by Katherine Harvey. Interview about growing up in Salmon Cove (00:27) biographic information; (02:45) sports; (05:46) knives; (08:29) first job; (11:04) bonfire night; (21:57) terrified rock; (26:05) Sylvie's Hill; (31:00) the woman in white; (34:09) fairies; (35:45) religion; (39:05) sliding; (41:19) healers; (44:32) warts